Hsa_circ_0001859 promotes NSCLC progression through the miRNA-101-3p/MMP1 axis - Tan, Jianxin; Fan, Zhenyu; Lu, Rongguo; Ye, Shugao (Frontiers in Oncology, 2025)
BackgroundNon-small cell lung cancer (NSCLC) is a prevalent form of lung cancer characterized by a significant incidence and mortality rate in China. Most patients are diagnosed at an advanced stage. Circ_0001859 served as an exon circular RNA, but its specific role in NSCLC remained extensively unexplored.MethodsQuantitative Real-Time-Polymerase Chain Reaction (qRT-PCR) and western blotting were utilized to detect messenger RNA (mRNA) and protein expression levels in NSCLC tissues and cells. Cell proliferation was assessed by Cell Counting Kit-8 (CCK-8) and colony formation assays. Cell migration and invasion were evaluated by transwell assay. Mechanistically, the mechanisms and target binding relationship between circ_0001859, miR-101-3p and MMP1 were assessed through the luciferase reporter and RNA immunoprecipitation (RIP) assays. In vivo xenograft model was established to examine the impact of circ_0001859.ResultsCirc_0001859 was significantly overexpressed in NSCLC tissues and cells. Functional studies demonstrated that silencing circ_0001859 significantly impeded the malignant phenotype of NSCLC cells. Bioinformatics analysis and rescue experiments disclosed that circ_0001859 functioned as a sponge for miR-101-3p, modulating MMP1 expression and thereby controlling NSCLC development and metastasis. The role of circ_0001859/miR-101-3p/MMP1 axis was validated in xenograft tumor models in vivo.ConclusionsOur research findings demonstrated that circ_0001859 engaged in regulating NSCLC growth and metastasis via the miR-101-3p/MMP1 pathway. These studies presented the first investigation into the precise function and putative regulatory mechanism of circ_0001859 in NSCLC, providing valuable insights towards prognostic indicators and therapeutic targets for malignant tumors.